Auctions - Sigrid Müller (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2000)
This paper surveys the literature on auctions. To a large part it is concerned with revenue and efficiency considerations. It addresses the problems of finding the auction that yields the greatest expected revenues to the auctioneer and that allocates the good(s) to the bidders which value them most highly. Models with private value, common value and general value will be considered. Open (English, Dutch) and sealed-bid (discriminatory, uniform-price, first-price, Vickrey) auctions are analysed. The analysis focuses on the strategic aspect of the bidding process, i.e. the game-theoretic auction literature will be heavily relied on. The employed equilibrium concept is Bayes-Nash. The theoretical analysis is supplemented by reviewing empirical work resulting from real-life auctions or controlled laboratory experiments. The importance of auctions in designing trading institutions is documented for financial markets.
urn:nbn:de:kobv:11-10047985
Keywords: 330